Cultural Literacy and Civic Education in Multicultural Universities in Indonesia and Malaysia - Pranata, Alvira; Syamsijulianto, Tri (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
Higher education institutions in culturally diverse societies have a vital role in fostering citizenship that is inclusive, democratic, and responsive to cultural differences. In Southeast Asia, especially in postcolonial settings such as Indonesia and Malaysia, civic education is commonly framed as a means of reinforcing national identity. However, this approach often fails to adequately recognize the varied cultural backgrounds and lived experiences of students. This study explores the ways cultural literacy is incorporated into civic education within higher education and examines its influence on the formation of students civic identities in multicultural learning settings. Adopting a qualitative case study approach, the research was carried out at two public universities, one located in Indonesia and the other in Malaysia, chosen for their culturally diverse student populations and involvement in civic oriented programs. Data collection involved document analysis, semi structured interviews with 24 lecturers, curriculum developers, and students, along with classroom observations conducted over a three month period. Thematic analysis identified an ongoing gap between civic education objectives at the policy level and everyday classroom practices, particularly in negotiating national narratives alongside cultural diversity. The findings reveal tensions between state centered civic models and culturally responsive teaching approaches, while also highlighting effective practices such as community based learning, student led discussions, and the inclusion of local wisdom. This study contends that cultural literacy, supported by strategic empathy and critical reflection, is central to promoting meaningful civic participation and inclusive forms of citizenship. By emphasizing students lived cultural experiences, this research contributes to broader discussions on transformative civic education and provides practical insights for advancing culturally grounded and socially just civic learning in higher education contexts across the Global South.